Effects of child long-term illness on maternal employment: longitudinal findings from the UK Millennium Cohort Study. (26th August 2016) - Hope, Steven; Pearce, Anna; Whitehead, Margaret; Law, Catherine
Abstract : Background: Maternal employment has increased in European countries, but levels of employment are lower among mothers whose children have a limiting long-term illness or disability. However, we do not know whether having a child with a limiting illness prevents take-up or maintenance of paid employment or whether 'common causes', such as lack of qualifications or maternal disability lead to both maternal unemployment and childhood illness. Longitudinal data have the potential to distinguish between these. Methods: We analyzed four waves (3, 5, 7 and 11 years) of the Millennium Cohort Study (MCS) to examine the relationship between childhood limiting illness and maternal employment, unadjusted and adjusted for covariates. Multinomial regression models were used to test the association between child illness and trajectories of maternal employment. Fixed effects models assessed whether a new report of a child illness increased the odds of a mother exiting employment. Results: At every wave, maternal employment was more likely if the child did not have a limiting illness. After adjustment for covariates, childhood illness was associated with risks of continuous non-employment (adjusted Relative Risk Ratio = 1.46 [Confidence Interval: 1.21, 1.76]) or disrupted employment (aRRR = 1.26 [CI: 1.06, 1.49]), compared with entering or maintaining employment. If a child developed a limiting long-term illness, the likelihood of their mother exiting employment increased (adjusted Odds Ratio = 1.27 [CI: 1.05, 1.54]). Conclusions: 'Common causes' did not fully account for the association between child illness and maternal employment. Having a child with a limiting illness potentially reduces maternal employment opportunities.